Bond behavior of NSM CFRP laminates in concrete under sustained loading. (20th July 2018) - Emara, M.; Barris, C.; Baena, M.; Torres, L.; Barros, J.
Highlights: The long-term bond behavior of NSM system was investigated using pull-out tests. Different sustained loading levels, bonded lengths and groove thicknesses were used. An analytical methodology simulating the long-term bond behavior was developed. Abstract: The success of Fiber Reinforced Polymers (FRP) strengthening methodologies for reinforcing concrete structures is highly related to the interfacial bond properties between reinforcement and concrete, which depends upon a number of parameters. Several studies were carried out investigating the short-term bond behavior of Near Surface Mounted (NSM) FRP strengthening systems. However, there has been only limited investigation of its long-term behavior resulting in a significant lack of available experimental data about this relevant aspect. The bond performance of the materials involved in the NSM FRP strengthening system (FRP, adhesive and concrete), due to its nature, is susceptible to be affected by both the sustained loading and environmental conditions. In this study, bond of NSM Carbon FRP (CFRP) laminates in concrete was investigated experimentally using pull-out tests. The experimental program consisted of both short-term tests, in which the load was applied monotonically up to failure, and long-term tests in which different levels of sustained loading were applied. The specimens were tested under sustained loading using bonded length, adhesive thickness and sustained loading level as the main parameters of the study. Results in terms of slip evolution with time are presented to explore the effects of the studied parameters on the long-term bond behavior between NSM CFRP laminates and concrete. Moreover, an analytical procedure to predict the slip variation versus time is proposed and compared to experimental results.